Pemberdayaan Masyarakat melalui Budidaya Lebah dalam Meningkatkan Kreativitas Pemuda: Community Empowerment through Bee Cultivation in Increasing Youth Creativity - Deswalantri Deswalantri; Rinovian Rais; Asfahani Asfahani (Edujavare Publishing, 2023)
This research aims to explore the potential for community empowerment through bee cultivation activities, especially in the context of increasing youth creativity. Bees not only provide economic benefits through honey production, but also have the potential to strengthen social networks and increase the creativity of the younger generation. This research method includes participatory surveys, in-depth interviews, and field observations to collect data on beekeeping practices and their impact on society, especially youth. Data analysis was carried out using a qualitative approach to understand the complex dynamics of interactions between bee cultivation, community empowerment and the development of youth creativity. The research results show that beekeeping not only provides additional income for people, but also increases their understanding of the environment and ecology. Additionally, these activities encourage collaboration between older generations and youth, creating space for the exchange of knowledge and skills. In the context of youth creativity, participation in beekeeping is identified as a stimulus that encourages youth to develop creative, innovative and leadership thinking skills. Youth involved in these activities show an increase in new ideas, the courage to take risks, and the ability to adapt in facing challenges. This research presents theoretical and practical contributions by detailing the potential for community empowerment through beekeeping as an innovative way to increase youth creativity. Policy implications and practical recommendations are also discussed to support further development of this empowerment model in the context of beekeeping in communities.